Screen Time and Cardiovascular Risks Among Middle-Aged Women. Issue 6 (November 2019) - Ham, Ok Kyung; Lee, Bo Gyeong
Abstract : Background: Screen time is a marker of sedentary behavior that threatens the health of women. Extended screen time is associated with depression, insomnia, cardiovascular disease, and decreased quality of life. Objective: In this study, we examined the factors associated with screen time and whether screen time is associated with the physiological and psychosocial health of middle-aged women. We applied a psycho-socioeconomic biobehavioral model of health and studied the outcomes of cardiometabolic biomarkers, insomnia, and quality of life. Methods: Secondary data analysis was performed using data from a cross-sectional study conducted with 423 women between 40 and 65 years of age. Socioeconomic, physiological, psychosocial, and behavioral characteristics were measured. Self-reported screen time during the past week was measured using an ordinal scale. The data were analyzed using multivariate analysis of covariance, analysis of covariance, and logistic regression analysis. Results: Twenty-four percent of subjects had at least 3 hours per day of screen time on weekdays, whereas 30.7% had at least 3 hours per day on weekends. Older women, unemployed women, and those who do not perform regular exercise were more likely to have at least 3 hours per day of screen time ( P < .05). Screen time was associated with total cholesterol and low-density lipoprotein cholesterol levels, insomnia, and menopause-specific quality of life ( P < .05). Conclusions: Based on a psycho-socioeconomic biobehavioral framework, we found that screen time is associated with the physiological and psychosocial health of women independent of socioeconomic and biobehavioral variables. Efforts to reduce the amount of screen time targeting middle-aged women will help improve cardiometabolic biomarkers and quality of life.